Determination of copper in sugarcane spirit by flame atomic absorption spectrometry using a ternary solvent mixture (water-ethanol-acetone) - De Souza, Joaõ Carlos [UNESP]; Toci, Aline Theodoro; Beluomini, Maísa Azevedo [UNESP]; De Paula Eiras, Sebastiaõ (Ecletica Quimica, 2017)
The present work describes the use of a homogeneous ternary mixture of the solvents water, ethanol, and acetone to improve the determination of copper in sugarcane spirit by flame atomic absorption spectrometry. The solvent ratio used (on a volume basis) was 5.0:5.0:15.0 (water:ethanol:acetone). The analytical curve for copper was linear up to a concentration of 6.00 mg L-1 of copper, and could be described by the equation: δAbs = 0.1778CCu + 0.0048 (r2 = 0.9999), and limits of detection and quantification (calculated using the standard deviation of the blank) were 0.01 and 0.05 mg L-1 of copper, respectively. Use of the proposed homogeneous ternary solvent system provided good stability and a significant increase in sensitivity compared to reference methodology. This increase in sensitivity enables the detection of smaller quantities of copper in sugarcane spirit. The method was applied to determine copper in commercial brands of sugarcane spirits. The results obtained by the proposed method were favorably compared with those given by the reference method.
Keywords: CopperSugarcane spirit; Flame atomic absorption spectrometry; Homogeneous ternary solvent mixture; Single phase solution